Secondary Prevention Using Cholesterol-Lowering Medications in Patients with Prior Atherosclerotic Cardiovascular Disease Events: A Retrospective Cohort Analysis - Xue Han; Steven Fox; Michelle Chu; Jeff McCombs (Journal of Health Economics and Outcomes Research)
**Background:** Secondary prevention with lipid-lowering medications in patients with atherosclerotic cardiovascular disease (ASCVD) is known to reduce the risk of clinical events and death. Current guidelines codify recommendations for implementing secondary prevention in appropriate patients. However, in real-world practice, secondary prevention is frequently initiated only after the patient experiences a cardiovascular-related hospitalization. The impact of these delays is not well known.